Managing trade credit risk: exporters’ view on the value of export credit insurance - Parkkinen, Ville-Pekka (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Companies face various risks when participating in international business. Even though exporting has been argued to represent low level of international commitment, exporters still face more risks in comparison to companies with purely domestic business activities. Among different risks lies credit risk which refers to possible non-payment or late payment of a customer. While exporters’ credit management is responsible for controlling credit risk, credit management in an international environment requires exporters to cope with incomplete information about customers’ creditworthiness and risks related to customers’ home countries. Even though there are various ways to conduct credit management, exporters may choose to acquire export credit insurance to support their credit management practices. By acquiring export credit insurance, exporters can hedge credit risk to credit insurers. This mitigates exporters’ exposure to credit risk if their customers fail to pay for purchased goods or services i.e. in case when credit risk realizes. This study explored exporters’ views on the value that export credit insurance provides for credit management practices. In this study, value refers to the benefit or benefits that export credit insurance provides. Theoretical background of the study includes literature relating to themes such as export credit insurance, credit management and risks related to internationalization. The study applied a qualitative research approach through five expert interviews from two Finnish exporters and one private export credit insurer. Expert interviews were considered as the most suitable method to collect data in order to create in-depth understanding of an underresearched topic, compare interviewees’ perceptions with current literature as well as to reveal new perceptions towards the value that export credit insurance provides for exporters and their credit management. Based on the existing literature and empirical research, it can be concluded that exporters see that export credit insurance provides value mainly through risk transfer. Risk transfer may also enable exporters to gain additional benefits such as expanding export sales to destinations where they have not sold before. In addition, export credit insurance can enable exporters to outsource a part of their credit management to credit insurers and to provide clear guidelines for exporters that have sufficient resources for independent credit management practices. On the contrary, it seems that exporters’ value perceptions towards export credit insurance are dependent on the extent of insurance coverage that exporters have for their customer base. At the same time, exporters may easily question the premise of export credit insurance if the level of customer non-payments is low.